Pengaruh Daya Tarik Wisata dan Fasilitas Terhadap Keputusan Berkunjung di Pantai Tanjung Kelayang - Hidayat, Taufiq; Surwandi, Wira (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
Tanjung Kelayang Beach is one of the main destinations that tourists must visit when traveling to Belitung. Various activities such as enjoying the beach scenery, swimming, snorkeling, and diving serve as major attractions. This study aims to examine the influence of tourist attractions and facilities on tourists' visiting decisions at Tanjung Kelayang Beach. A quantitative research method was applied, utilizing multiple linear regression analysis with data collected from 100 respondents. The results show that both tourist attractions and facilities are rated positively, falling into the